2012
DOI: 10.5923/j.re.20120204.02
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of ‘<i>Fanya juu’</i> Soil Conservation Structure on Selected Soil Physical & Chemical Properties: the Case of Goromti Watershed, Western Ethiopia

Abstract: Soil degradation is evident in the mountainous areas of Ethiopia, is often represented as results of human pressure. It can be improved through different Soil and Water Conservation (SWC) measures. The study was conducted in Goromti watershed, in western Ethiopia to evaluate the impact of Fanya juu structures on some soil physical & chemical properties. Cultivated fields treated by five years and ten years old fanyajuu structures were compared with non conserved cultivated land (control) and evaluated under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
49
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 20 publications
13
49
4
Order By: Relevance
“…These findings are in agreement with those of Adgo et al (2013) and Assefa (2007) who found similar results for the Anjeni Watershed (Table 1). Likewise, these results (Table 1) concur with several authors who concluded that soils in the Ethiopian highlands are acidic (Chibsa and Ta, 2009;Demelash and Stahr, 2010;Feoli et al, 2002) and that its soil organic carbon pool is depleted (Hailu et al, 2012;Taddese, 2001;Zeleke et al, 2004). Soil acidity in the region is partly due to continuous weathering processes and leaching of base cations (Amare et al, 2013;Hodnett and Tomasella, 2002), while depletion of soil organic carbon is further acerbated by scarcity of farm inputs (including organic biomass) among other factors (Abegaz and Van Keulen, 2009;Feoli et al, 2002;Taddese, 2001).…”
Section: Soil Physical Propertiessupporting
confidence: 93%
“…These findings are in agreement with those of Adgo et al (2013) and Assefa (2007) who found similar results for the Anjeni Watershed (Table 1). Likewise, these results (Table 1) concur with several authors who concluded that soils in the Ethiopian highlands are acidic (Chibsa and Ta, 2009;Demelash and Stahr, 2010;Feoli et al, 2002) and that its soil organic carbon pool is depleted (Hailu et al, 2012;Taddese, 2001;Zeleke et al, 2004). Soil acidity in the region is partly due to continuous weathering processes and leaching of base cations (Amare et al, 2013;Hodnett and Tomasella, 2002), while depletion of soil organic carbon is further acerbated by scarcity of farm inputs (including organic biomass) among other factors (Abegaz and Van Keulen, 2009;Feoli et al, 2002;Taddese, 2001).…”
Section: Soil Physical Propertiessupporting
confidence: 93%
“…In contrast, several researchers (e.g. Million, ; Demelash & Stahr, ; Gebreselassie et al ., ; Mekuria et al ., ; Hailu et al ., ; Amare et al ., ) reported significant differences in SOC concentration among soils with and without SWC treatment.…”
Section: Resultsmentioning
confidence: 98%
“…Shiene () also observed a significant increase in SOC concentration with an increase in slope gradient in northeast Ethiopia (in the North and South Wello zones of the Amhara region). Other researchers (e.g., Assefa, ; Hailu et al ., ; Amare et al ., ) reported an opposite trend of SOC concentration against slope. In the non‐conserved sub‐watershed, on the other hand, the highest SOC concentration was observed on the crest slope and the lowest on the foot slope.…”
Section: Resultsmentioning
confidence: 98%
“…Other methodological error is that, not to accounted land loss by physical SWC practices which ranges from 8 to 15%. Vancampenhout et al (2006), Nyangena and Köhlin (2008), Alemayehu et al (2006), Hailu et al (2012) and Damene, (2012) classify watershed in to upper and lower and to different slope class and fail to consider individual farm variability. In this regard Abay (2011) reported increase of crop yield due to SWC practices differs from farmer to farmer as the management of soil is different among different farmers.…”
Section: Methods Of Studymentioning
confidence: 99%
“…Many said nothing about maintenance of SWC in their study area (Hailu et al, 2012;Mihrete, 2014;Challa et al, 2016) and age of SWC practices (Alemayehu et al, 2006). Management practice such as increasing the height of bunds can influence bund effectiveness (Nyssen et al, 2007).…”
Section: Response Time Of Swc Practices and Managementmentioning
confidence: 99%